Superconductivity in the ternary iridium–arsenide BaIr2As2. (12th January 2017) - Wang, Xiao-Chuan; Ruan, Bin-Bin; Yu, Jia; Pan, Bo-Jin; Mu, Qing-Ge; Liu, Tong; Chen, Gen-Fu; Ren, Zhi-An
Abstract: Here we report the synthesis and discovery of superconductivity in a novel ternary iridium–arsenide compound BaIr2 As2 . The polycrystalline BaIr2 As2 sample was first synthesized by a high temperature and high pressure method. Crystal structural analysis indicates that BaIr2 As2 crystallizes in the ThCr2 Si2 -type layered tetragonal structure with space group I 4 /mmm (No. 139), and the lattice parameters were refined to be a = 4.052(9) Å and c = 12.787(8) Å. By the electrical resistivity and magnetic susceptibility measurements we found type-II superconductivity in the new BaIr2 As2 compound with a T c (critical temperature) of 2.45 K, and an upper critical field μ 0 H c2 (0) about 0.2 T. Low temperature specific heat measurements gave a Debye temperature of about 202 K and a distinct specific jump with Δ C e /γT c = 1.36, which is close to the value of BCS weak coupling limit and confirms the bulk superconductivity in this new BaIr2 As2 compound.